A Study Examining the Effects of Oil Export in Iran - Mehdi, Safdari (Journal of Social and Development Sciences, 2011)
The effect of increasing oil incomes on oil exporter countries is the main issues of political economy. Generally and especially about Iran can be recognized this effect in the government spending method, economic structure and behavior of government within the country. Since oil incomes arenâ€™t result of the performance of economic activities, consequently increasing does not show the real economic prosperity. The purpose of this study is to determine the relationship between oil exports and economic growth in Iran. The data were collected from 1961-2006 and were analyzed using Cointegration, Error Correction Model, and VEC Granger causality/Wald Exogeniety model. The result of the analyses showed that there was significant relationship between oil incomes and economic growth. It showed that increasing in oil price rate lead to increasing in the government costs consequently it affect on the exchange rate and lead to increasing in real exchange rate. Therefore oil incomes are regarded as an important factor in Iran’s economic growth.